RECREATION SCHOOL IN ELEMENTARY EDUCATION I: CHALLENGES FOR INCLUSION OF 6 YEARS OLD CHILD (Fiep Bulletin - online, 2016)
A major challenge to school with the expansion of education to nine years will be the host of children under six years in elementary schools. The organization of time, space and people are distinct hindering the process of adapting these students in this new stage of education. We believe that recess is a time present in everyday school life largely unexplored as an area for the construction of knowledge, civility and interpersonal relations. The scope of this study is to report the experience of motórias challenging activities propositions in the organization of school time and recreational spaces in the elementary school of EMEF Antonio de Alcantara Machado affecting the recreation of daily life and interpersonal relationships.